Treatment of a Paediatric Distal Femoral Malunion Deformity - Pavarotti, Greta S.; Boudrieau, Randy J. (Veterinary and Comparative Orthopaedics and Traumatology, 2018)
Objective The aim of this article was to describe the surgical re-alignment technique and stabilization of a distal femoral deformity in a 6-week-old, male, Foxhound.Methods A healing metaphyseal fracture, resulting in a valgus deformity with internal rotation, was observed just proximal to the distal femoral physis. The deformity was treated by an opening wedge osteotomy with lateral translation and external rotation of the distal epiphysis using a guide-wire technique; a corticocancellous allograft bridged the defect, which was stabilized with a 2.0-mm locking Y-plate designed for human phalangeal fractures.Results Successful deformity correction was obtained with subsequent healing of the osteotomy and maintained longitudinal bone growth. Sciatic neurapraxia developed as a result of a migrating adjunct pin (9 days post-operatively), which was removed. At long-term follow-up (4 years), a 12% shortening of the femur did result in addition to an asymptomatic grade 2 medial patellar luxation (MPL). The cause of the MPL was not evident; the owners declined treatment and the dog continued to function as an active hunting dog.Clinical Significance Prior to ossification of the epiphyses in very young animals, which precludes effective radiographic pre-planning, the guide-wire technique can be utilized as the primary tool for performing angular deformity correction. Adequate fixation and stabilization can be obtained with small human specialty locking plates.
Keywords: bone growth; fracture fixation; growth deformities and correction; locking plates; paediatric orthopaedics